Substance Release from Polyelectrolyte Microcapsules - Musin, Egor V.; Kim, Aleksandr L.; Tikhonenko, Sergey A. (Encyclopedia (Basel, Switzerland), 2022)
Controlled release of substance from polyelectrolyte microcapsules is a triggered degradation of the microcapsule membrane that is extensive enough to release the contained substances out into the environment. Membrane degradation can be a result of enzymatic digestion, ultrasound or light exposure, heating, application of a magnetic field, pH or ionic strength changes in the solution or bacteria-mediated processes. This technology can be used for the targeted release of drugs, and for the development of self-healing materials and new generation pesticides.